Clinical Approach to Pediatric Transverse Myelitis, Neuromyelitis Optica Spectrum Disorder and Acute Flaccid Myelitis - Wang, Cynthia (Children (Basel), 2019)
Pediatric transverse myelitis (TM) is an acquired, immune-mediated disorder that leads to injury of the spinal cord and often manifests as weakness, numbness, bowel dysfunction, and/or bladder dysfunction. Multiple etiologies for myelitis can result in a similar clinical presentation, including idiopathic transverse myelitis (TM), multiple sclerosis (MS), neuromyeltis optica spectrum disorder (NMOSD) associated with anti-aquaporin 4 antibodies, MOG antibody-associated disease, and acute flaccid myelitis (AFM). Diagnosis relies on clinical recognition of the syndrome and confirming inflammation through imaging and/or laboratory studies. Acute treatment is targeted at decreasing immune-mediated injury, and chronic preventative therapy may be indicated if TM is determined to be a manifestation of a relapsing disorder (i.e., NMOSD). Timely recognition and treatment of acute transverse myelitis is essential, as it can be associated with significant morbidity and long-term disability.